Hubungan Penggunaan Media Pembelajaran dengan Minat Belajar Matematika Siswa Kelas IV SD Gugus II - Adnan K; Muhammad Idris Jafar; Muhammad Irfan; Musdalifah Musdalifah (Universitas Negeri Makassar, 2022)
The problem studied in this study is the relationship between the use of learning media and interest learning mathematics. This research is correlational quantitative research that aims to determine significant relationship between the use of instructional media and interest learning mathematics students class IV SD Cluster II. Data was obtained by distributing questionnaires. The results showed that there was a significant relationship between the use of instructional media and interest learning mathematics class IV SD Cluster II with rcount (0.586) > rtable (0.212), which means H1 accepted. Based on results study, it can be found that the use of learning media has impact on student responses so that it affects interest learning, especially mathematics. So, increase the use of media, the students' interest learning will increases. The resulting impact is known that the use media according to characteristics and objectives can increase interest learning so that obtain good learning outcomes.